Noncutaneous Melanoma - Scott, Jeffrey F; Gerstenblith, Meg R (Exon Publications, 2018)
Noncutaneous Melanoma integrates the expertise of a multidisciplinary group of clinicians and investigators to help shed light on recent advances in the understanding of noncutaneous melanomas. The authors skillfully present a comprehensive review of uveal melanoma, the most common type of ocular melanoma, as well as nasopharyngeal, genitourinary, and anorectal melanoma, and finally melanoma of unknown primary. This book will be highly valuable to clinicians caring for patients with noncutaneous melanoma who desire a review of the current literature regarding these entities. As the diagnostic and therapeutic approaches to these patients are continually evolving, it is imperative for clinicians to stay well versed on new advances gleaned from the primary literature. This book addresses each topic in sophisticated detail, and it will be a valuable resource for clinicians and investigators to assist in patient care and guide further research.